Polymeric nanoparticles for RNA delivery - Jiang, Xingya; Abedi, Kimia; Shi, Jinjun (Reference Module in Materials Science and Materials Engineering, 2023)
As exemplified by recent clinical approval of RNA drugs including the latest COVID-19 mRNA vaccines, RNA therapy has demonstrated great promise as an emerging medicine. Central to the success of RNA therapy is the delivery of RNA molecules into the right cells at the right location. While the clinical success of nanotechnology in RNA therapy has been limited to lipid-based nanoparticles currently, polymers, due to their tunability and robustness, have also evolved as a class of promising material for the delivery of various therapeutics including RNAs. This article overviews different types of polymers used in RNA delivery and the methods for the formulation of polymeric nanoparticles and highlights recent progress of polymeric nanoparticle-based RNA therapy. [Display omitted]